PENGARUH PENGGUNAAN MEDIA ANIMASI GAMBAR TERHADAP PEMAHAMAN KONSEP PECAHAN SISWA - Kusuma, Rendra Sakbana (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2019)
This research focused to use of animated media images using powerpoint and its effect on understanding the mathematical concepts of 4th grade students in elementary school.The purpose of this study are, 1) How is elementary school mathematics learning using picture animation media?, and 2) Is there a significant influence between the media of animated images using PowerPoint to the understanding of mathematics concepts of 4th grade elementary school students? The research method used is a quantitative research approach in the form of experimental research pre-experimental designs with one-group pretest-posttest design models. Analysis of the data used refers to the formulation of the problem, including the comparison test using the t-test formula and the correlation test using the product moment formula. Comparative test is used to answer descriptive problem formulation and correlation test to answer associative problem formulation that has been raised by previous research.Based on the results of data analysis using statistics with the t-test formula and product moment correlation, it is concluded that: 1) the use of 3-dimensional animation media with PowerPoint is very good and more than expected, and 2) the use of 3-dimensional animation media with PowerPoint has an influence which is significant to the understanding of the concept of fractions of class IV SD Negeri Banyuaju.